2018
DOI: 10.1016/j.cie.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance policy optimisation for multi-component systems considering degradation of components and imperfect maintenance actions

Abstract: This article proposes a stochastic optimisation model in order to reduce the long-term total maintenance cost of complex systems. The proposed work is based on the following approaches: (i) optimisation of a cost model for complex multi-component systems consisting of preventive and corrective maintenance using reliability analysis, which faces two different maintenance policies (periodic block-type and age-based) and (ii) a clustering method for maintenance actions to decrease the total maintenance cost of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 37 publications
(60 reference statements)
0
29
0
Order By: Relevance
“…Recently, the advance in computational algorithm and computer science have helped to solve and optimize the complicated problem [76][77], but the number of parameters is finite and simulation time isn't acceptable for some of the real-time systems. Industry 4.0 context provides big data and on the other hands, dynamic and resilience structures need the real-time response; thus optimization algorithms must be improved.…”
Section: Fig 4 Generic Architecture With H-cpps Control Loop [69]mentioning
confidence: 99%
“…Recently, the advance in computational algorithm and computer science have helped to solve and optimize the complicated problem [76][77], but the number of parameters is finite and simulation time isn't acceptable for some of the real-time systems. Industry 4.0 context provides big data and on the other hands, dynamic and resilience structures need the real-time response; thus optimization algorithms must be improved.…”
Section: Fig 4 Generic Architecture With H-cpps Control Loop [69]mentioning
confidence: 99%
“…In other words Cmax j represents the IJQRM cost of the required resources to get the highest quality maintenance and to restore the reliability function of the component to its nominal value, R j ¼ 1. As a consequence, when the budget of a maintenance action for the jth component is equivalent to Cmax j , the executed maintenance action consists of replacing the component with a new one; hence, the value of the age reduction is restored, α ¼ 0 (Martinod et al, 2018).…”
Section: Development Formulation Of the Service Problemmentioning
confidence: 99%
“…In this paper, the proposed work analyses the demand for transport, for an optimal service-oriented maintenance plan; thus, the maintenance policy represents a set of parameters to qualitatively evaluate the proposed solution. Other work (Martinod et al , 2018) proposes a stochastic optimisation model in order to reduce the long-term total maintenance cost of complex systems considering several maintenance policies, but does not take into account the service-operational policy. The lack of studies evaluating service performance, as impacted by maintenance requirements, provided a motivation for the research.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing interest in the maintenance modeling of multi-unit systems (Eruguz, Tan, & van Houtum, 2017;Martinod, Bistorin, Castañeda, & Rezg, 2018;Poppe, Boute, & Lambrecht, 2018;Zhang & Zeng, 2015). A review of the CBM policies for systems with multiple components can be found in Keizer, Flapper, and Teunter (2017).…”
Section: Introductionmentioning
confidence: 99%